The impact of teachers’ assessment practices on students’ acquisition of process skills and performance in basic science - Achor, Emmanuel Edoja; Agogo, Peter Ogbu; Musa, Joyce Hassana (American Journal of Education and Learning, 2024)
The purpose of this study is to examine impact of teachers’ assessment practices on students’ acquisition of process skills and performance in basic science in Kogi State, Nigeria, utilizing a cross-sectional survey research design. The sample comprises 393 Basic Eight students from a population of 20,885 in the study area using the multi-stage sampling procedure. Ten Basic Science teachers were observed in class. Data collection instruments include the Basic Science Process Skill Acquisition Test (BSPSAT), the Basic Science Performance Test (BSPT), and the Basic Science Teachers’ Assessment Practices Observation Scale (BSTAPOS). The reliability coefficients were 0.71 for BSPSAT, 0.86 for BSPT using Kuder–Richardson Formula 21, and the BSTAPOS value was 0.66 using Spearman’s rank correlation. The descriptive statistics of mean and standard deviation as well as an independent t-test and analysis of variance (ANOVA) were used for analysis. Significant differences were found regarding the impact of teachers’ low, moderate, and high classroom assessment practices on the mean process skills acquisition scores and the mean performance scores of students in basic science. Students’ gender did not show a significant difference regarding the impact of teachers’ low, moderate, and high assessment practices on process skills acquisition and performance scores in basic science. It is recommended that teachers of basic science should use assessment guides and workbooks to acquaint themselves with the appropriate assessment practices.